Development Of A DC Motor Control - Hazal, Nasrul Hadi (Universiti Sains Malaysia, 2017)
A DC motor can operates without any driver but by doing so, the motor will be robbed of is full potential such as having a better speed control. With that in mind, this project was done by having 3 objectives to solve the issue. One of it is to develop a DC motor drive and control system based on Genuino Uno microcontroller with LCD display and keypad interface. Another one is to integrate a close-loop PID control to the system to improve the performance of motor control under load or without load. Last but not least is to implement the modules and control system into a single, simple DC motor control prototype and test its performance. Based on those objectives, a methodology was planned including circuit drawing, code writing, and constructing the prototype, and testing the controller performance. The testing was divided into 2 parts: no load analysis and under load analysis with each part tested on different controller scheme. The performance parameters that were considered in the evaluation are the settling time, percentage of overshoot, and error response time. The parameters were compared for motor with open-loop driver, P controller, PI controller, and PID controller driver. From the result, PID controller and PI controller were found to have better performance compared to all the other control methods. PI controller has better settling time and error response time but has a huge percentage of overshoot while PID controller has slower settling time and error response time but smaller percentage of overshoot compared to PI controller.